1996
DOI: 10.1074/jbc.271.35.21273
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cAMP Binding Site Mutations on the Interaction of cAMP Receptor Protein with Cyclic Nucleoside Monophosphate Ligands and DNA

Abstract: Although cAMP binding to wild type cAMP receptor protein (CRP) induces specific DNA binding and activates transcription, cyclic nucleoside monophosphate (cNMP) binding to the CRP mutant Ser 128 3 Ala does not, whereas the double CRP mutant Thr 127 3 Leu/ Ser 128 3 Ala activates transcription even in the absence of cNMP. Isothermal titration calorimetry measurements on the cNMP binding reactions to the S128A and T127L/S128A mutants show that the reactions are mainly entropically driven as is cAMP binding to CRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Consistent with this interpretation, the substitution of Ser-128 by Ala in E. coli CRP abolishes cooperative cAMP binding (48). …”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Consistent with this interpretation, the substitution of Ser-128 by Ala in E. coli CRP abolishes cooperative cAMP binding (48). …”
Section: Discussionmentioning
confidence: 76%
“…coli CRP, where DNA-binding affinity is enhanced by several orders of magnitude in the presence of 0.1 m m cAMP, allowing specific DNA binding at nanomolar concentrations (27, 48). For CRP Mt , a much less significant enhancement of DNA binding was observed, and higher concentrations of cAMP compared with E.…”
Section: Discussionmentioning
confidence: 99%
“…Since cAMP enhances the monomer-monomer interaction in CRP (1), the closed form must be favored by a stronger interaction between the monomers in CRP. The amino acid sequence along the monomer-monomer helical interface exhibits an almost perfect leucine zipper motif consisting of a heptad repeat of leucine residues along one face of the helix with the exception of a Met 120 and Thr 127 (6). In the T127L mutant, Thr 127 is replaced by Leu, thereby creating a more perfect leucine zipper which would lead to stronger association between the monomeric units as is observed in other leucine zipper proteins (30).…”
Section: Discussionmentioning
confidence: 97%
“…Since it has been shown from isothermal titration calorimetry (ITC) measurements that changes in the in vivo transcriptional activity arising from these interfacial mutations are not dependent on the binding affinity of the cyclic nucleotide monophosphate (cNMP) to the CRP-mutant (6), the transcriptional activity of cNMP-ligated CRP-mutants may depend on the influence of these interfacial mutations on the binding of the operon to CRP. It is, thus, important to determine the thermodynamics of DNA binding to CRP and its T127L, S128A, and CRP* mutants.…”
mentioning
confidence: 99%
“…In addition, the mutation of Thr 127 to Cys, Ile, or Ser also resulted in the enhancement of in vivo and in vitro transcription in the presence of cGMP, and it was concluded that the Thr 127 3 Cys, Ile, and Ser mutations in CRP produced structural changes in CRP similar to those induced by cAMP binding to CRP (3). Since the binding affinities of cAMP to CRP and the CRP mutants are nearly the same (3,4), changes in the enhancement of transcription by CRP must involve processes subsequent to the binding of cAMP to CRP. A recent isothermal titration calorimetric (ITC) study of the binding of three 40-bp DNA duplexes with each one containing the CRP binding site sequence of a promoter to cNMP-ligated CRP, T127L, S128A, and CRP* revealed large differences in the CRP binding site affinities, which could account for differences in the enhancement of transcription by the cNMP-ligated CRP mutants (5).…”
mentioning
confidence: 99%